Advances in commercial deployment of spoken dialog systems - Suendermann, David (SpringerBriefs in electrical and computer engineering, 2011)
Advances in Commercial Deployment of Spoken Dialog Systems covers the peculiarities of commercial deployments of spoken dialog systems, from the tools, standards, and design principles to build them, the infrastructure to deploy them, techniques to monitor, evaluate, and analyze them, and, most importantly, effective strategies to adapt, tune, and optimize them. The book shows to what extent academic spoken dialog system research converges with real-world applications. This academic and practical synergy can be leveraged to build successful and robust spoken dialog applications that are useful when dealing with the dynamics of the ever-changing future user.